Удосконалення механізмів реалізації державної податкової політики в України - Спасіченко, Данило Сергійович; Spasichenko, Danylo Serhiyovych (Ірпінь, 2024)
В роботі узагальнено актуальні проблеми у цій сфері, а саме: необхідність підвищення ефективності податкових перевірок, зменшення кількості помилок під час їх проведення та прийняття вмотивованих рішень за їх результатами, вдосконалення наявних та розробка нових показників оцінки ефективності контрольної роботи податкових органів

The work summarizes the current problems in this area, namely: the need to increase the efficiency of tax audits, reduce the number errors during their implementation and making motivated decisions based on their results, improvement of existing and development of new indicators for assessing the effectiveness of the control work of tax authorities
Improvement of mechanisms for the implementation of state tax policy in Ukraine
Keywords: податкова політика; податкова система; оцінка стану; податкові надходження; економіка України; tax policy; tax system; state assessment; tax revenues; economy of Ukraine